1996
DOI: 10.1021/om950635k
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Sodium Bis(N-aryliminophosphoranyl)alkanides with Halide-Bridged Platinum(II) and Palladium(II) Phosphine Dimers Affording Four-Membered M−N−P−C Metallacycles and Orthometalated Platinum(II) and Palladium(II) Complexes

Abstract: Reaction of the sodium bis(iminophosphoranyl)alkanide compounds Na[CR‘‘(PPh2NC6H4R‘-4)2] (1a, R‘‘ = H, R‘ = CH3; 1b, R‘‘ = H, R‘ = OCH3; 1c, R‘‘ = CH3, R‘ = CH3) with M2X4(PR3)2 (M = Pt, Pd; X = Cl, Br; PR3 = PEt3, PMe2Ph) yields the four-membered metallacycles MX(PR3){CR‘‘(PPh2NC6H4R‘-4)2} (2a−f, M = Pt; 3a−c, M = Pd), containing the bis(iminophosphoranyl)alkanide ligand coordinated in a σ-C,σ-N chelating fashion. The molecular structure of 2e (X = Cl, PR3 = PMe2Ph, R‘‘ = CH3, R‘ = CH3) has been determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 82 publications
4
34
0
2
Order By: Relevance
“…Thus, it can be concluded that no interaction between phosphorus and sodium atoms is observed. The bond distances Na1-N1 2.3828(16), Na1-O1 2.3112 (17), and Na1-O2 2.3631(18) Å are in the range of previously reported values. 63 The P1-B1 bond distance (1.920(2) Å) remains almost unchanged compared to that of the free ligand 1-H (1.908(3) Å).…”
Section: Alkali Metal Complexessupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, it can be concluded that no interaction between phosphorus and sodium atoms is observed. The bond distances Na1-N1 2.3828(16), Na1-O1 2.3112 (17), and Na1-O2 2.3631(18) Å are in the range of previously reported values. 63 The P1-B1 bond distance (1.920(2) Å) remains almost unchanged compared to that of the free ligand 1-H (1.908(3) Å).…”
Section: Alkali Metal Complexessupporting
confidence: 74%
“…57,61 Chelation from ligand 1 to two sodium atoms via two amido nitrogen atoms and hydrogen atoms of the two BH 3 groups exhibits a tub-shaped Na 2 P 2 N 2 (BH 3 ) 2 core with mean bond angles N1-P1-B1 106.72 (9) • and N2-P2-B2 110.20 (9) • . The Na1-P1 3.3056(8) distance of 3.3056(8) Å is slightly longer than the bond distances of 2.9661 (17) 62 and it is larger than the sum of the covalent radii (3.00 Å) of 14, P1-B1-K1 106.16 (14), C13-K1-B1 64.34 (8), C13-N1-P1 127.5(2), K1 ′ -B1-K1 98.46(9), B1 ′ -K1-B1 81.54 (9). sodium and phosphorus.…”
Section: Alkali Metal Complexesmentioning
confidence: 79%
See 1 more Smart Citation
“…[10,21,22,23] The C(1), P(1), N(1), and P(2) atoms in 3 are coplanar as they are in 2. The P À N bond lengths in the {P=N=P} + fragment (1.607(2) and 1.583(2) ) and P-N-P angle (128.4(1)8) are similar to those in 2 (1.593(2) and 1.599(2) , and 123.2(2)8).…”
mentioning
confidence: 99%
“…[10,21,22,23] The C(1), P(1), N(1), and P(2) atoms in 3 are coplanar as they are in 2. [10,21,22,23] The C(1), P(1), N(1), and P(2) atoms in 3 are coplanar as they are in 2.…”
mentioning
confidence: 99%